Studi Komparasi Antara Hasil Belajar Siswa yang DiAjar dengan Metode Pembelajaran Student Teams Achievement Divisions (Stad) dan Mind Mapping - Moh. Asykuri (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
The purpose of this study is (1) To determine the presence and the absence of differences in learning outcomes in teaching students with learning using Student Teams Achievement Divisions (STAD) and Mind Mapping on the subjects In MI Islamic Cultural History MA’ARIF NU Brondong Lamongan Academic Year 2013/2014. (2) To determine student learning outcomes better between the aplication of learning methods Student Teams Achievement Divisions (STAD) and Mind Mapping on the subjects In grade IV MI Islamic Cultural History MA’ARIF NU Brondong Lamongan. This research method Pre-Experimental Design (two-groups pretest-posttest design). Subjects were fourth grade students of Madrasah Ibtida’iyah MA’ARIF NahdlotulUlama’ BrondongLamongan is divided into two classes, namely classes totaling 21 IV A and IV B classes totaling 20. The results of this study indicate that: (1) There is a difference in student learning outcomes in teaching learning methods using STAD and Mind Mapping. With the t-test calculation (Independent Sample T-test) obtained t value = 2,541 > 2,022 (t table) with number Sig. 0.015 < 0.05. (2) Learning outcomes of students who take learning Student Teams Achievement Divisions (STAD) is better than the learning outcomes of students who take learning Mind Mapping. With the results of the calculation of simple linear regression constants obtained experimental class 1 (STAD) is greater than the value of the constant experimental class 2 (Mind Mapping) which a1 = 64.008 > a2 = 58.504.